2010
DOI: 10.1111/j.1741-3729.2010.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Assets and Family Stress Among Low‐Income Families

Abstract: The “hard times” resulting from the 2008 Great Recession represent an opportunity to re-examine the theoretical framework for how families use economic resources to manage stress. M. Sherraden's (1991) theory of assets and H. I. McCubbin and J. Patterson's (1983) family adjustment and adaptation response model informed this study of how assets relate to family demands among 839 low-income families. Structural equation modeling found that assets were directly related to a reduced sense of family demands and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 32 publications
2
35
1
1
Order By: Relevance
“…Being under greater economic stress was associated with greater time spent in bill management for the full and white sample and greater savings behavior for the full, white, and black samples. With respect to savings, these findings are consistent with previous studies that have found attempts at savings to be associated with lower stress and the ability to save as a mediator between economic stress and individual and family outcomes (Dew, 2007;Rothwell & Han, 2010). Financial therapists should encourage clients to save money no matter how small the amount and regardless of the client's income level; any amount of savings has been associated with reduced financial hardship (Levine, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…Being under greater economic stress was associated with greater time spent in bill management for the full and white sample and greater savings behavior for the full, white, and black samples. With respect to savings, these findings are consistent with previous studies that have found attempts at savings to be associated with lower stress and the ability to save as a mediator between economic stress and individual and family outcomes (Dew, 2007;Rothwell & Han, 2010). Financial therapists should encourage clients to save money no matter how small the amount and regardless of the client's income level; any amount of savings has been associated with reduced financial hardship (Levine, 2016).…”
Section: Discussionsupporting
confidence: 80%
“…Income shocks are a consistent predictor of material hardship for households (Heflin 2016), yet among lowincome households, the presence of up to $2000 in liquid assets reduces the risk of hardship by 5 percentage points compared to households with no assets (McKernan et al 2009). Additional studies have found reduced odds for material hardship associated with Child Development Account (CDA) participation (Wikoff et al 2015) and reduced financial strain associated with homeownership (Manturuk et al 2012) and greater financial assets among low-income households (Rothwell and Han 2010). The available evidence suggests that household assets lessen risk for material hardship and may buffer the impact of financial shocks on hardship.…”
Section: Assets As a Mediator Of Financial Shocks And Hardshipmentioning
confidence: 99%
“…Assets are positively linked to a higher sense of well-being (Dew, 2007;Muntaner, Eaton, Diala, Kessler, & Sorlie, 1998) and negatively linked to the likelihood of additional financially problematic events occurring (Rothwell & Han, 2010). Consumer debt is also linked to higher levels of anxiety and economic pressure (Conger et al, 1993;Dew, 2007;Drentea, 2000).…”
Section: Financial Behaviors As a Moderatormentioning
confidence: 99%